(untitled) (Perner’s Contacts, 2016)
As well as in every engineering sector also in the design of rail vehicles tools for computer modelling and simulation are nowadays the most often used. In this way static analyses of rail vehicle components and dynamic analyses of a completed rail vehicle multibody system are possible to perform. Static analyses are most commonly carried out using the finite element method. Abreast of it the multibody system dynamics is investigated in other specialized software and methods. If we combine these two approaches we can improve multibody system of a rail vehicle and therefore to evaluate its behaviour and properties closer to reality. This contribution is focused on the preparing and implementation of flexible body into the multibody system of rail vehicle bogie. For this purpose the freight wagon bogie was chosen.